Validação de métodos para detecção da adição de suco de maçã em sucos de uva - Spinelli, Fernanda Rodrigues (My University, 2014)
Due to the increased consumption of grape juice, quality control is a reality in every country producers and consumers of this product. The most common form of adulteration is by substitution with apple juice. The adulterated samples can be identified by specific analyzes, as apple juice has some compounds that the grape does not have or has in small amounts, as phlorizin and sorbitol. Therefore, analytical methods capable of identifying the composition of grape juices and determine its authenticity are needed to ensure effective control of the quality of the grape juices. For this reason, the present study aimed to validate the analytical methods of phlorizin and sorbitol to detect addition of apple juice in grape juice. Initially, the methods were validated for the analysis of phlorizin and sorbitol, carried out in liquid chromatography. After validation of the methods, tests were conducted additions of apple juice cultivars Gala and Fugi in grape juices from cultivars Concord, Isabel and Bordô, and were analyzed grape and apple commercial juices. All grape juices show that high concentrations of sorbitol also showed high concentration of phlorizin. Through this study, it was observed that the methods of phlorizin and sorbitol are effective to detect the addition of apple juice grape juice.
Devido ao aumento do consumo de sucos de uva, o controle da qualidade é uma realidade em todos os países produtores e consumidores desse produto. A forma mais comum de adulteração é através da substituição por suco de maçã. As amostras adulteradas podem ser identificadas através de análises específicas, pois o suco de maçã possui alguns compostos que a uva não apresenta ou possui pequenas quantidades, como a florizina e o sorbitol. Portanto, métodos analíticos capazes de identificar a composição de sucos de uva e determinar sua autenticidade são necessários para garantir um controle eficaz da qualidade dos sucos de uva. Por esta razão, o presente trabalho teve como objetivo validar os métodos analíticos da florizina e do sorbitol para detectar adição de suco de maçã em suco de uva. Inicialmente, foram validados os métodos para análise de florizina e sorbitol, realizados em cromatografia líquida. Após a validação dos métodos, foram realizados testes de adições de suco de maçã das cultivares Gala e Fugi em sucos de uva das cultivares Concord, Isabel e Bordô, e, foram analisados sucos de uva e maçã comerciais. Todos os sucos de uva que apresentaram concentração elevada de sorbitol também apresentaram concentração elevada de florizina. Através dos resultados deste estudo, observou-se que os métodos da florizina e do sorbitol são eficazes para detectar a adição de suco de maçã em suco de uva.
Keywords: Suco de uva; Suco de maçã; Biotecnologia; Grape juice; Apple juice